2016
DOI: 10.1016/j.drugalcdep.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The profile of psychiatric symptoms exacerbated by methamphetamine use

Abstract: Methods: 164 methamphetamine users, who did not meet DSM-IV criteria for a lifetime primary psychotic disorder, were followed monthly for one year to assess the relationship between days of methamphetamine use and symptom severity on the 24-item Brief Psychiatric Rating Scale.Exacerbation of psychiatric symptoms with methamphetamine use was quantified using random coefficient models. The dimensions of symptom exacerbation were examined using principal axis factoring and a latent profile analysis. Results:Sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 39 publications
(49 reference statements)
2
52
0
Order By: Relevance
“…In the absence of a collateral history, meth/amphetamine‐induced psychosis is almost indistinguishable from acute schizophrenia, making a diagnosis based on presenting signs and symptoms challenging. In our study we found that the ED nurses frequently reported signs and symptoms of agitation in most of the people who tested positive for any substance.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a collateral history, meth/amphetamine‐induced psychosis is almost indistinguishable from acute schizophrenia, making a diagnosis based on presenting signs and symptoms challenging. In our study we found that the ED nurses frequently reported signs and symptoms of agitation in most of the people who tested positive for any substance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have not examined cognitive predictors in relation to the intensity of stimulant use during treatment. This is critical, as previous research has found a dose-response relationship between methamphetamine use and poorer outcomes (Lappin et al 2016;McKetin et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, high rates of premorbid psychiatric conditions, including major depression and psychotic disorders , occur amongst people who are dependent on methamphetamine. Conversely, methamphetamine dependence is associated with an exacerbation of symptoms in psychotic disorders , the occurrence of psychotic symptoms even in people who do not have a psychotic disorder , and increases in the severity of depression and suicidality . Symptoms of self‐neglect (e.g.…”
Section: Discussionmentioning
confidence: 99%